Vezérfonal a szintézisíráshoz 4. A Rákosi-diktatúra kora, 1948-1956.: Első rész: A két munkáspárt egyesülésétől a desztalinizálás kezdetéig, 1948. június 12 - 1953. július 18. - Gulyás, László (Közép-Európai Közlemények, 2024)
In a previous study – Thoughts on the national-civil-conservative synthesis of „short Hungarian 20th century” history – that laid the foundation for writing synthesis – we designated the era boundaries of the Rákosi dict(atorship as follows: the starting point is June 12, 1948, the day when the Hungarian Workers’ Party (MDP) was created from the „merger” of the MKP and the SZDP. While the end point was July 18, 1956, the day when Rákosi relieved of his position as first secretary of the MDP and traveled to the Soviet Union, from where he could never return to Hungary. In this study, we present the important events that took place between these points. With this, we ourline the short history of the Rákosi dictatorship.